1997
DOI: 10.1111/j.1432-2277.1997.tb00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Responses to exercise in heart and kidney transplant patients

Abstract: There is a lack of information about renal responses in heart and kidney transplant patients after intense physical exercise. Eleven heart and ten kidney transplant recipients, as well as two control groups of healthy subjects, were given a maximum exercise test on a bicycle ergometer. One control group was also given a moderate load corresponding to the peak load of the kidney transplant group. Blood and urine samples were collected before and after exercise and assayed for lactate, creatinine, total protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
10
1
1
Order By: Relevance
“…Despite improved survival, the aerobic capacity of renal transplant recipients (RTR), measured objectively as peak exercise oxygen uptake (V O 2peak ), is 10% to 40% lower than age-matched healthy individuals (Kempeneers et al 1990;Poortmans et al 1997;Warburton et al 2004;van den Ham et al 2005van den Ham et al , 2007Armstrong et al 2006;Kouidi et al 2013). The mechanisms responsible for the reduced V O 2peak are due to impaired cardiovascular and skeletal muscle function that results in reduced oxygen delivery to and (or) utilization by the exercising muscles (Armstrong et al 2006;Oterdoom et al 2008;Zelle et al 2011;Kouidi et al 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Despite improved survival, the aerobic capacity of renal transplant recipients (RTR), measured objectively as peak exercise oxygen uptake (V O 2peak ), is 10% to 40% lower than age-matched healthy individuals (Kempeneers et al 1990;Poortmans et al 1997;Warburton et al 2004;van den Ham et al 2005van den Ham et al , 2007Armstrong et al 2006;Kouidi et al 2013). The mechanisms responsible for the reduced V O 2peak are due to impaired cardiovascular and skeletal muscle function that results in reduced oxygen delivery to and (or) utilization by the exercising muscles (Armstrong et al 2006;Oterdoom et al 2008;Zelle et al 2011;Kouidi et al 2013).…”
Section: Introductionmentioning
confidence: 95%
“…There is no specific physical activity recommendation for kidney transplant recipients, but also no restrictions for performing activities . In the absence of a disease specific guideline, the American College of Sports Medicine (ACSM) recommends adults with clinically significant chronic conditions to comply with the same guidelines as healthy adults as much as their abilities and conditions allow .…”
mentioning
confidence: 99%
“…While the understanding of renal function following exercise is important in healthy individuals, its knowledge is essential in patients with existing renal complications. Early work (10) demonstrated that moderate exercise increased plasma creatinine by ~10% in patients with a kidney transplant, although exercise had no detrimental effect on renal function. Further research is needed to fully understand acute renal changes following exercise in CKD groups.…”
Section: Exercisementioning
confidence: 99%